2011
DOI: 10.1371/journal.pone.0025594
|View full text |Cite
|
Sign up to set email alerts
|

Big Defensins, a Diverse Family of Antimicrobial Peptides That Follows Different Patterns of Expression in Hemocytes of the Oyster Crassostrea gigas

Abstract: BackgroundBig defensin is an antimicrobial peptide composed of a highly hydrophobic N-terminal region and a cationic C-terminal region containing six cysteine residues involved in three internal disulfide bridges. While big defensin sequences have been reported in various mollusk species, few studies have been devoted to their sequence diversity, gene organization and their expression in response to microbial infections.FindingsUsing the high-throughput Digital Gene Expression approach, we have identified in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 42 publications
0
97
2
Order By: Relevance
“…Allam et al (2006) reported a rapid increase (within 72 h) of circulating hemocytes in V. philippinarum after injection of Vibrio tapetis and V. anguillarum. In general, expression of marine mollusk defensin transcripts is known to be induced by bacterial challenges (Adhya et al, 2012;De Zoysa et al, 2010;Rosa et al, 2011;Zhao et al, 2007Zhao et al, , 2010. However, there are some reports of decreased transcriptional responses of mollusk defensins against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Allam et al (2006) reported a rapid increase (within 72 h) of circulating hemocytes in V. philippinarum after injection of Vibrio tapetis and V. anguillarum. In general, expression of marine mollusk defensin transcripts is known to be induced by bacterial challenges (Adhya et al, 2012;De Zoysa et al, 2010;Rosa et al, 2011;Zhao et al, 2007Zhao et al, , 2010. However, there are some reports of decreased transcriptional responses of mollusk defensins against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…2A). This result was surprising given the strong Vibrio induced increase in Cg-bigdef1 reported by Rosa et al (2011) We also quantified Cg-bpi1, which encodes for the AMP bactericidalpermeability-increasing protein. BPI's activities are a result of its ability to permeabilize bacterial membranes (Gonzalez et al, 2007b) due to their affinity for binding to lipopolysaccharides found on the outer membrane of gram-negative bacteria (Elsbach & Weiss, 1998;Levy, 2000).…”
Section: Expression Of Ampsmentioning
confidence: 87%
“…Defensins (Cg-defh1-2) are a prominent group of AMPs, which are also ubiquitously distributed across unicellular and multicellular organismal groups (Schmitt et al, 2010). Representatives of a separate family of 'big' defensins have also been characterized in C. gigas (Cg-bigdef1, Cgbigdef2 and Cg-bigdef3;Rosa et al, 2011). These 'big' defensins are a group of AMPs predominantly found in mollsucs, and are genetically and structurally more similar to vertebrate defensins than to the invertebrate defensins (Rosa at el., 2011).…”
Section: Expression Of Immune-related Gene Transcriptsmentioning
confidence: 99%
See 2 more Smart Citations